Studi Teknik Tradisional Budidaya dan Produksi Kenanga Jawa (Cananga odorata f. macrophylla) di Blitar - Hariadi Propantoko; Irdika Mansur; Arum Sekar Wulandari (Jurnal Silvikultur Tropika, 2020)
Java kenanga or kenanga (Cananga odorata f. macrophylla) is a tropical and sub-tropical tree species that grows naturally in Indonesia and produces essential oil. This species has been cultivated in the past by community in Indonesia, mainly on their yard. The population of kenanga has decreased significantly, but in Blitar district the community is still doing cultivating the species although in a small scale. The purpose of this research is to observe the cultivation efforts by the community and also kenanga flower production in Blitar district. This research was conducted by interviewing farmers and observation of kenanga trees in the field. The results showed that cultivation efforts being made to improve the production of kenanga flower is by pruning, fertilizing, flowering routine and retrieval or emoval of kenanga fruit. The average kananga flower production reached 381 kg / year / tree in the age group above 11 years. Factors that affect flower production were tree age (years), total tree height (m), diameter at breast height (cm) and the width tree canopy (m2). The most significant factors affecting flower production were tree diameter and width of tree canopy. Cultivation efforts being made to improve the production of kenanga flower is by pruning, fertilizing, flowering routine and retrieval or removal of kenanga fruit. Keywords: Cananga odorata f. macrophylla, essential oil, cultivation, Blitar